Efficient epoxide isomerization within a self-assembled hexameric organic capsule. Issue 87 (5th September 2016) - Caneva, Thomas; Sperni, Laura; Strukul, Giorgio; Scarso, Alessandro
Abstract : The supramolecular organic nano-capsule formed by the self-assembly of six resorcin[4]arene units efficiently promotes the isomerization of epoxides (Meinwald isomerization) to the corresponding carbonyl compounds. Abstract : The isomerization of epoxides to the corresponding carbonyl compounds is efficiently catalyzed by the supramolecular organic nano-capsule formed by the self-assembly of six resorcin[4]arene units. The capsule provides a combination of weak Brønsted acidity and a suitable nano-environment that favors the metal-free isomerization reaction.